PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR SISWA PADA MATERI KERAGAMAN BUDAYA INDONESIA KELAS IV SD NEGERI 101773 KOLAM T.A 2023/2024 - Aulia, Dina; Simbolon, Naeklan; Simanjuntak, Sorta; Sitohang, Risma; Siregar, Fajar Sidik (Universitas Negeri Medan, 2024)
This research aims to determine the effect of the Discovery Learning learning model assisted by Wordwall media on student learning outcomes on the material of Indonesian Cultural Diversity in Class IV SD Negeri 101773 Kolam T.A 2023/2024. This type of research is quantitative research with experimental method Pre-Experimental design type One Group Pretest-Posttest Design. The research was conducted in class IV A as many as 30 students. The research instrument was a multiple choice test of 20 items. The data analysis technique used was normality test, and hypothesis testing. From the pretest data analysis, 5 students were complete with a percentage of 16.7% and 24 students were not complete with a percentage of 83.3%, and the average pretest score was 49.17 with the highest score of 80, the lowest score was 20. After being treated and given a posttest, it was found that the posttest scores of students in the complete category were 24 students with a percentage of 80% and 6 students in the incomplete category with a percentage of 20%, for an average score on the posttest of 75.17 with the highest score of 95, the lowest score of 55. The results of the calculation of the hypothesis obtained t_hitung> t_tabel, namely 2.591> 2.045 at the 5% significant level, then Ho is rejected and Ha is accepted which states that there is an effect of the Discovery Learning learning model assisted by Wordwall media on student learning outcomes on the material of Indonesian Cultural Diversity in Class IV SD Negeri 101773 Kolam T.A 2023/2024.Keywords: Discovery Learning, Wordwall, Learning Outcomes